Mindfulness dan Kecerdasan Emosional sebagai Prediktor Self-Efficacy Siswa SMA: Pendekatan Psikologis dan Pendidikan - Lie, Nie; Suherman, Heru; Utomo, Budi; Partono, Partono; Kabri, Kabri (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyze the role of mindfulness and emotional intelligence as predictors of high school students' self-efficacy in the context of education and psychology. Self-efficacy is an important factor that influences students' motivation, perseverance and academic achievement. The research subjects consisted of various studies analyzed using the Systematic Literature Review (SLR) approach, with the method of searching for articles from internationally reputable databases covering open journals from 2020 to 2024. The results showed that mindfulness contributed to increasing self-efficacy through improving students' emotion regulation, stress management, and focus of attention. Meanwhile, emotional intelligence plays a role in strengthening students' self-efficacy in facing academic and social challenges through more adaptive emotion management. The combination of these two factors creates a synergistic effect that increases self-efficacy more optimally than if only one of the factors is strengthened. The findings provide practical implications for the development of a more holistic educational curriculum by incorporating mindfulness and emotional intelligence-based programs as strategies to improve students' self-efficacy.